Carnival in Brazil as production of health care: narratives from a samba school community. (30th September 2020) - Cordeiro, M; Santos, D; Magalhães, F; Martins, G; Barbosa, J; Riquieri, M; Silva, M; Andrade, M; Ferreira, B; Lima, R
Abstract: Introduction: Carnival is a popular festival that was introduced in Brazil from the European heritage. However, it was the enslaved African people who saw forms and processes of resistance for the construction of identity during this festive period. The reframing and resistance that blacks establish with carnival is the result of a cultural need to stay alive both as a subject and as a collective. This is how samba schools emerge in the urban peripheries of Rio de Janeiro as a form of artistic, cultural and leisure production. Associations acquire for themselves the role of the State in providing access to rights that many are denied, neglected or scrapped. In these schools, it is possible to observe a relationship of belonging and donation ("principle of gift") on the part of their so-called community, they are passions and meanings that produce relationships of self-care reaffirmation of intersubjectivity. Objective: This work aims to identify the carnival as a space for the production of projects, resistances and protagonisms and to analyze the meanings of the subjective processes of health, disease, care and carnival, through the narratives of a samba school community. Methodology: This is an exploratory analysis of a qualitative approach in public health. A samba school was chosen from the special group of the capixaba carnival, which is located in a peripheral region. We will use it to define snowball technical sampling. The data will be collected through semi-structured interviews and on-site observations by the researcher. The data analysis methodology used will be discourse analysis. Expected Results: It is expected to understand the different practices and processes of health, disease, care and carnival, among a peripheral community that is part of a samba school. Key messages: This work aims to analyze health care about a cultural aspect of marginalized populations and how health policies are related to carnival. Impact on the production of knowledge about popular culture and health.